Menyingkapi Penerapan PSAK116 Terhadap Rasio Keuangan Berbasis Kemampuan Bayar: Studi Kasus Pada PT Mitra Adiperkasa Tbk - Rizaldi, Fredy; Agus Munandar (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
The adoption of PSAK 116 changes the accounting treatment of leases by recognising right-of-use assets and lease liabilities, replacing operating lease expenses with depreciation and interest. These changes have a direct impact on ability-to-pay financial ratios such as Debt Service Coverage Ratio (DSCR) and Net Debt to EBITDA. This study analyses the financial statements of PT Mitra Adiperkasa Tbk (MAPA) for 2019-2024 using a descriptive-comparative and simulation approach in case PSAK 116 is not applied. The results show a technical increase in EBITDA due to PSAK 116, which has an effect on the apparent improvement of DSCR and Net Debt to EBITDA. Simulations using the PSAK 30 approach show more conservative and realistic ratios. These findings highlight the importance of understanding the impact of accounting standards on ratio interpretation and credit decision-making.